Pengaruh Return On Equity, Current Ratio, Dan Sales Growth Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening - Rafida Nur Fadila; Vicky Oktavia; Dwi Eko Waluyo; Maria Safitri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the effect of Return on Equity (ROE), Current Ratio (CR), and Sales Growth on firm value with dividend policy as an intervening variable in mining companies listed on the Indonesia Stock Exchange during the 2020–2025 period. Firm value is proxied by Price to Book Value (PBV), while dividend policy is measured using the Dividend Payout Ratio (DPR). This research uses a quantitative approach with secondary data obtained from the annual financial reports of mining companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, and the data were analyzed using path analysis. The results show that Return on Equity (ROE) has a positive and significant effect on firm value, while Current Ratio (CR) and Sales Growth do not have a significant effect on firm value. Return on Equity (ROE) and Current Ratio (CR) positively affect dividend policy, whereas Sales Growth does not affect dividend policy. Dividend policy has a positive and significant effect on firm value. Furthermore, dividend policy is able to mediate the effect of Return on Equity (ROE) and Current Ratio (CR) on firm value, but it is unable to mediate the effect of Sales Growth on firm value. This study is expected to contribute theoretically to the development of financial management literature and practically to assist company management and investors in making decisions related to profitability, liquidity, sales growth, dividend policy, and firm value.